Eye Movement Desensitization and Reprocessing (EMDR) Therapy on a Patient with Schizophrenia and Clinical Effects: A Case Study - (:unkn) unknown (TURKIYE SINIR VE RUH SAGLIGI DERNEGI, 2017)
Being exposed to traumatic experiences is rather common in patients with schizophrenia. Adverse experiences may induce the onset of psychotic symptoms or trigger current symptoms to be exacerbated. Eye Movement Desensitization Reprocessing (EMDR) is an effective therapy in the treatment of incidences with underlying traumatic experiences, there by it can be conducted on various cases in addition to other treatments such as psycho-medication or another therapy method. It was developed by Shapiro in 1980s. Although desensitization is widely applied on patients with Post-Traumatic Stress Disorder, it is unusual for EMDR therapy to be safely and effectively performed in the treatment of psychotic disorder sor symptoms. In the present case study, EMDR treatment process and course of psychiatric state in a patient with history of child hood abuse and forced psychiatric residency will be discussed. The patient who had a diagnosis of schizophrenia for 8 years was treated with antipsychotic treatment as well as 2 sessions of EMDR, and as a result, a positive change was observed in her general clinical course. Our thoughts on this phenomenon are that EMDR treatment is an effective, safe and short-term intervention in the comorbidity of PTSD and psychotic disorders. However, the literature about the place of EMDR in the treatment of schizophrenia cases is rather limited and much more research is needed.
Keywords: Eye movement desensitization reprocessing (EMDR); psychotic disorders; schizophrenia; forced hospitalization; traumatic events; PSYCHOSIS; TRAUMA; SYMPTOMS; PTSD